PENINGKATAN PERAN BEA CUKAI DALAM MENDORONG EKSPOR KOMODITAS PERIKANAN: STUDI KASUS DI WILAYAH MALUKU - HIMAWAN YUSUF (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2019)
Maluku is a national fish barn, so the low number of fisheries exports from Maluku is of concern to all parties, including Customs. The purpose of this study is to analyze the causes of low fisheries commodity exports from Maluku and the role that Customs can take to increase fisheries commodity exports in Maluku. This research uses qualitative methods, by data and stakeholders’ opinions. The results of the study show that the complexity of licensing and poor service are the main causes. The results also show that Customs can take a greater role to encourage fisheries commodity exports with its resources. The implication of this research is to be a trigger for all Customs Offices to increase their role in intensifying the economy in the regions by followingith their respective regional potential.